Audio/visual recording of doctors in hospitals: Guideline from the Association of Anaesthetists. (2nd March 2020) - Yentis, S. M.; Shinde, S.; Bogod, D.; Flatt, N.; Hartley, H.; Keats, P.; Leifer, S.; Pappachan, J.; Parfitt, E.; Pooni, J.; Rowland, A.
Summary: Guidelines are presented that summarise the legal position regarding the audio/visual recording of doctors and others in hospitals. In general, there are few, if any, legal grounds for refusing a request by patients to record procedures and/or discussions with clinicians, although some staff may feel uncomfortable being recorded. Trusts and others are advised to draw up local policies and ensure staff and patients are adequately informed.